2016
DOI: 10.1186/s12877-016-0350-y
|View full text |Cite
|
Sign up to set email alerts
|

Physical, social, psychological and existential trajectories of loss and adaptation towards the end of life for older people living with frailty: a serial interview study

Abstract: BackgroundThe experiences of people with cancer and organ disease have been described across different dimensions of need as they approach death. Such information is lacking for frail older people approaching death, but could highlight how a palliative approach might be relevant for this population.MethodsCognitively intact, community dwelling adults considered to be moderately or severely frail were recruited from a medical day hospital. Those recruited nominated an informal carer and case-linked professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 46 publications
3
77
1
1
Order By: Relevance
“…shopping, gardening, crosswords) and internal processes (e.g. accepting decline and interdependency) to maintain positive well‐being (Birkeland & Natvig, ; Boggatz & Meinhart, ; D'Avanzo et al., ; Holm & Severinsson, ; Lloyd et al., ; Lommi et al., ; Menichetti & Graffigna, ; Nicholson, Meyer, Flatley, Holman, & Lowton, ; Warmoth et al., ). Our study showed that people with mild frailty, whose needs have not previously been explored, engage in similar health promotion activities and have similar motivational barriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…shopping, gardening, crosswords) and internal processes (e.g. accepting decline and interdependency) to maintain positive well‐being (Birkeland & Natvig, ; Boggatz & Meinhart, ; D'Avanzo et al., ; Holm & Severinsson, ; Lloyd et al., ; Lommi et al., ; Menichetti & Graffigna, ; Nicholson, Meyer, Flatley, Holman, & Lowton, ; Warmoth et al., ). Our study showed that people with mild frailty, whose needs have not previously been explored, engage in similar health promotion activities and have similar motivational barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Older people's views have been widely canvassed regarding self‐care, health promotion and lived experiences of frailty (Birkeland & Natvig, ; Lloyd, Kendall, Starr, & Murray, ; Lommi, Matarese, Alvaro, Piredda, & De Marinis, ; Menichetti & Graffigna, ). However, to our knowledge, no study has focussed specifically on community‐dwelling populations with mild frailty in the United Kingdom (UK), explored the acceptability of different health promotion behaviours or offered practical recommendations for designing new health promotion services.…”
Section: Introductionmentioning
confidence: 99%
“…Some older people reach a tipping point when they feel unable to live usefully or with dignity and experience increasing psychological and existential distress before dying. 21 Actions to promote optimum physical health should be combined with help to engage with social support and care that let frail older people maintain a sense of self and purpose even in the face of increasing dependence. Allowing older people to raise and discuss their greatest fears-of losing independence, dementia, or being a burden to others-is person centred early palliative care.…”
Section: Gradual Declinementioning
confidence: 99%
“…The content and the context of such conversations should be relevant to the person's current state and involve those close to them (box 1). [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Many clinicians find it challenging to raise palliative care with patients because it is associated with imminent death. In Canada and the UK some palliative medicine physicians use the term "supportive care" to promote access.…”
Section: Good Conversationsmentioning
confidence: 99%
“…230 The MoCA is scored continuously out of 30, with ≥ 26 considered normal 230 and has good sensitivity and specificity for detecting mild cognitive impairment and mild Alzheimer's disease. 183 The MoCA was research assistant administered at baseline and 6 months. We did not exclude participants on the basis of their MoCA scores, only if they lacked capacity to consent.…”
Section: Cognitionmentioning
confidence: 99%